Scientific and Practical Meeting dedicated to 110th Anniversary of Sytenko Institute of Spine and Joint Pathology and International Educational Course «Primary and Revision hip and Knee Joint Replacement» - Korolkov, Oleksandr; Bondarenko, Stanislav; Golubeva, Inna; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
On October 4-5, 2017, events took place in Kharkiv on the occasion of the 110th anniversary of the State Institution "Institute of Spine and Joint Pathology named after Professor MI Sitenko National Academy of Medical Sciences of Ukraine "